Economic growth and environmental quality in a post-pandemic world : new directions in the econometrics of the environmental Kuznets Curve - Shahbaz, Muhammad; Balsalobre-Lorente, Daniel; Sharma, Rajesh (Professor of economics) (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"In response to the damage caused by a growth-led global economy, researchers across the world started investigating the association between environmental pollution and its possible determinants using different models and techniques. Most famously, the Environmental Kuznets Curve hypothesises an inverted U-shaped association between environmental quality and GDP. This book explores the latest literature on the Environmental Kuznets Curve including developments in the methodology, the impacts of the pandemic and other recent findings. Researchers have recently broadened the range of the list of drivers of environmental pollution under consideration which now includes variables such as foreign direct investment, trade expansion, financial development, human activities, population growth, and renewable and nonrenewable energy resources, all of which vary across different countries and times. And in addition to C02 emissions, other proxies for environmental quality - such as water, land and ecological footprints - have been used in recent studies. This book also incorporates analysis of the relationship between economic growth and the environment during the Covid-19 crisis presenting new empirical work on the impact of the pandemic on energy use, the financial sector, trade and tourism. Collectively, these developments have improved the direction and extent of the Environmental Kuznets Curve hypothesis and broadened the basket of dependent and independent variables which may be incorporated. This book will be invaluable reading for researchers in environmental economics and econometrics"--
Keywords: Environmental economics -- Econometric models; Economic development -- Environmental aspects -- Econometric models; BUSINESS & ECONOMICS / Economics / General; BUSINESS & ECONOMICS / Environmental Economics